The Ethics of Using Information and Communication Technology (ICT) in Online Product Marketing in Jati Village, Tarogong District, Garut Regency - Rosliani, Elin; Rahayu, Dinar; Nugraha, Yopi; Habil, Riski (Indonesian Journal of Community Empowerment (IJCE), 2023)
In the current digital era, the use of social media has become an integral part of people's lives. However, this technological advancement also brings challenges and impacts that need to be addressed, particularly at the local level, such as in Desa Jati, Tarogong District, Garut Regency. The purpose of this research is to understand the ethics of using information and communication technology (ICT) in online product marketing and to promote wise use of social media at the village level. This research will employ a qualitative approach with a case study method. Data will be collected through interviews with various relevant stakeholders in Desa Jati, Tarogong District, including the village head, Village Consultative Body (BPD) members such as small and medium enterprises (SMEs), villagers, youth groups, community leaders, and local government officials. Additionally, content analysis of social media will be conducted to observe usage patterns and their impact on the village community. The results of this study are expected to provide a deeper understanding of the challenges and opportunities in building a wise digital society at the village level, as well as the ethics involved. Furthermore, strategies, education, and concrete steps will be proposed to ensure ethical practices in online promotion for the village, as it faces social changes resulting from digital technology advancements.